2017
DOI: 10.1073/pnas.1712302115
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic regulation of trafficking to Caenorhabditis elegans sensory cilia by a Retinal Degeneration 3 homolog and retromer

Abstract: Sensory neurons often possess cilia with elaborate membrane structures that are adapted to the sensory modality of the host cell. Mechanisms that target sensory transduction proteins to these specialized membrane domains remain poorly understood. Here, we show that a homolog of the human retinal dystrophy gene () is a Golgi-associated protein required for efficient trafficking of a sensory receptor, the receptor-type guanylate cyclase GCY-9, to cilia in chemosensory neurons of the nematode The trafficking defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 75 publications
1
4
0
Order By: Relevance
“…In addition, GCY-22::GFP was more diffuse in the cell body and dendrite (Supplementary Fig. 1,3), in agreement with RDL-1 regulating an early trafficking pathway for GCYs 43 .…”
Section: Gfpsupporting
confidence: 75%
See 1 more Smart Citation
“…In addition, GCY-22::GFP was more diffuse in the cell body and dendrite (Supplementary Fig. 1,3), in agreement with RDL-1 regulating an early trafficking pathway for GCYs 43 .…”
Section: Gfpsupporting
confidence: 75%
“…The C. elegans RD3 orthologue, RDL-1, influences the trafficking of GCYs to the PCMC and cilium 43 .…”
Section: Gfpmentioning
confidence: 99%
“…Low brood numbers, such as we observed in our vps-26 knockout worms, can also be correlated with defects in ciliogenesis, albeit in a 3D culture environment (Lee et al, 2016). Moreover, a recent study indicates that ciliogenesis in C. elegans BAG sensory neurons is coordinated by retromer-mediated vesicular trafficking (Martinez-Velazquez and Ringstad, 2018). Two recent studies in mammalian hint at the potential involvement of the retromer complex in ciliogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the role of the retromer complex has been studied extensively in yeast and in mammalian systems, the function of retromer and its role in development in invertebrates such as C. elegans is incompletely understood. It has been observed that worms with mutant vps-29 or vps-35 genes display impaired trafficking of the receptor-type guanylate cyclase GCY-9, which accumulates in BAG chemosensory neurons (Coudreuse et al, 2006; Martinez-Velazquez and Ringstad, 2018). Recent studies have shown a role for worm retromer subunits in anteroposterior polarity, Wnt signaling and Q cell migration (Prasad and Clark, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is rather tempting to speculate that some of the conserved N- and/or C-proximal portions of the RD3 molecule are specifically required for the cyclase trafficking, such as by playing the role of a recognition signal or participating in the interactions with the trafficking machinery, after the high-affinity binding of RD3 to the cyclase has occurred via the interface identified in our present study. Experimental evaluation of such a possibility may also help shed light on additional biological processes potentially involving RD3, because some recent reports suggest that RD3 (or its homologs) can also interact with other trafficked or nontrafficked proteins ( 45 , 46 ), and not only in the retina but also perhaps in different organs of vertebrate and invertebrate species.…”
Section: Discussionmentioning
confidence: 99%